Pakcoy Quality Change Study (Brassica rapa L.) in LDPE Packaging (Low Density Polyethylene) With Two Methods Pre Cooling During Cold Storage - Lady C. Ch. E. Lengkey; Iis Wahyunandita Akume; Ireine A. Longdong (Jurnal Agroekoteknologi Terapan, 2023)
Pakcoy vegetables after harvest will change in quality, so it is necessary to handle post-harvest. The pre-cooling method is one of the methods that can be done to prevent these quality changes, the goal is to extend the shelf life of pakcoy. The quality of pakcoy is influenced by environmental conditions during storage. Suitable packaging can prevent the rate of respiration. Respiration can cause a deterioration in the quality of the pakcoy, so before storage it needs to be packaged. This study aims to determine the duration of pakcoy storage packaged with LDPE plastic clips based on changes in weight, moisture content, color, and texture during cold storage in 2 (two) pre-cooling methods, namely room cooling and hydro cooling and comparing the quality of pakcoy carried out pre-cooling with room cooling and hydro cooling methods. This study used experimental methods with pre-cooling treatment, namely room cooling and hydro cooling, data collection was carried out as many as 3 samples per treatment. The data is presented in tables and graphs and then analyzed descriptively. The results showed that pakcoy using the hydro cooling method can be stored for 22 days while using the room cooling method can be stored for 18 days. Pakcoy quality is obtained better in hydro cooling treatment. Keywords: Pakcoy vegetables;  post-harvest;  respiration; Abstrak Sayuran pakcoy setelah panen akan terjadi perubahan mutu, sehingga perlu adanya penanganan pascapanen. Metode pra pendinginan adalah salah satu metode yang dapat dilakukan untuk mencegah perubahan mutu tersebut, tujuannya adalah memperpanjang masa simpan pakcoy. Mutu pakcoy dipengaruhi oleh kondisi lingkungan selama   penyimpanan.  Pengemasan yang sesuai dapat mencegah laju respirasi. Respirasi dapat menyebabkan kemunduran mutu pada pakcoy, sehingga sebelum melakukan penyimpanan perlu dikemas. Penelitian ini bertujuan untuk menentukan lama penyimpanan pakcoy yang dikemas dengan plastik klip LDPE berdasarkan perubahan bobot, kadar air, warna dan tekstur selama penyimpanan dingin pada 2 (dua) metode pra pendinginan yaitu room cooling dan hydro cooling serta membandingkan mutu pakcoy yang dilakukan pra pendinginan dengan metode room cooling dan hydro cooling. Penelitian ini menggunakan metode eksperimen dengan perlakuan pra pendinginan yaitu room cooling dan hydro cooling, pengambilan data dilakukan sebanyak 3 sampel setiap perlakuan. Data disajikan dalam tabel dan grafik kemudian dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa pakcoy menggunakan metode hydro cooling dapat disimpan selama 22 hari  sedangkan  dengan menggunakan metode room cooling dapat disimpan selama 18 hari. Diperoleh mutu pakcoy lebih baik pada perlakuan hydro cooling. Kata Kunci: Sayuran pakcoy;  pascapanen; Respirasi;